Does Incident Circumcision Lead to Risk Compensation? Evidence From a Population Cohort in KwaZulu-Natal, South Africa. (1st March 2019) - Ortblad, Katrina F.; Harling, Guy; Chimbindi, Natsayi; Tanser, Frank; Salomon, Joshua A.; Bärnighausen, Till
Abstract : Background: Voluntary medical male circumcision reduces men's risk of HIV acquisition and may thus increase HIV risk-related sexual behaviors through risk compensation. We analyze longitudinal data from one of Africa's largest population cohorts using fixed-effects panel estimation to measure the effect of incident circumcision on sexual behaviors. Setting: KwaZulu-Natal, South Africa. Methods: An open population cohort of men was followed from 2009 to 2015. Men self-reported their circumcision status and sexual behavior annually. We used linear regression models with individual-level fixed effects to measure the effect of incident circumcision on recent sex (past 12 months) and sexual behaviors that increase HIV risk (not using a condom at last sex, never using condoms with the most recent sexual partner, concurrent sexual partners at present, and multiple sexual partners in the past 12 months). We controlled for potential time-varying confounders: calendar year, age, education, and sexual debut. Results: The 5127 men in the cohort had a median age of 18 years (interquartile range 16–24) at cohort entry. Over the study period, almost 1 in 5 of these men (19.4%) became newly circumcised. Incident circumcision affected neither recent sex [percentage point (PP) change 0.0, 95% confidence interval: −1.2 to 1.3] nor sexual behaviors that increase HIV risk (PP −1.6, 95% confidence interval: −4.5 to 1.4). Conclusions: The data from this study strongly reject the hypothesis that circumcision affects sexual risk-taking. Risk compensation should not serve as an argument against increased and accelerated scale-up of circumcision in this and similar communities in South Africa. Abstract : Supplemental Digital Content is Available in the Text.